Peran Probiotik dan Sumbu Usus-Otak (Gut-Brain Axis) dalam Patogenesis dan Penatalaksanaan Depresi: Tinjauan Literatur - Herni Purwantari; Nila Authoria (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Depression is a mental disorder involving biological changes, including an imbalance in the gut microbiota. The gut-brain axis acts as a bidirectional communication system between the gut and the central nervous system through neural, immunological, endocrine, and metabolic pathways. This literature review aims to evaluate the role of the gut-brain axis and probiotics in the pathogenesis and management of depression. The review was conducted narratively using articles retrieved from Google Scholar, PubMed, and ScienceDirect, with 12 studies meeting the inclusion criteria. Results indicate that gut microbiota dysbiosis is associated with increased inflammation, impaired neurotransmitter regulation, changes in microbial metabolites, and dysfunctional gut-brain communication. Several studies have also reported that probiotic supplementation, particularly Lactobacillus and Bifidobacterium, has the potential to improve symptoms of depression and anxiety, improve sleep quality, and influence biological parameters related to the gut-brain axis. However, effectiveness varies depending on the strain, dose, and duration of intervention. Overall, the gut-brain axis plays a crucial role in the pathogenesis of depression, and probiotics have the potential to be used as adjunctive therapy by modulating the gut microbiota. However, large-scale clinical studies with more standardized designs are needed to confirm their effectiveness and mechanisms of action.